2003
DOI: 10.1182/blood-2003-01-0118
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and hematopoietic potential of side population cells throughout embryonic development

Abstract: Adult murine bone marrow hematopoietic stem cells (HSCs) can be purified by sorting Hoechst 33342-extruding side population (SP) cells. Herein we investigated whether SP cells reside within embryonic tissues and exhibit hematopoietic progenitor activity. We isolated yolk sac (YS) and embryonic tissues 7.5 to 11.5 days after coitus (dpc), resolved an SP in each, and demonstrated that these SP cells exhibit distinct phenotypic and functional characteristics throughout development. YS and embryonic SP isolated 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
92
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 35 publications
3
92
1
Order By: Relevance
“…In addition, we have also shown that hemogenic endothelial cells express markers of both endothelial and stem cells (Flk1 and cKit, respectively), but do not express the hematopoietic lineage marker, CD45 5,11,12 . Thus, hemogenic endothelial cells can be identified and isolated by FACS as Flk1+/cKit+/CD45-SP cells, and we have shown that these cells give rise to HSPC contained within the Flk1-/cKit+/CD45+ SP fraction of yolk sac and AGM cells 5,11,12 . Hemogenic endothelial cells and HSPC can be identified and isolated from yolk sac or AGM tissues harvested from either freshly euthanized embryos, or from embryos cultured for up to 48 hours in ex vivo embryo culture (as depicted in Figure 1).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…In addition, we have also shown that hemogenic endothelial cells express markers of both endothelial and stem cells (Flk1 and cKit, respectively), but do not express the hematopoietic lineage marker, CD45 5,11,12 . Thus, hemogenic endothelial cells can be identified and isolated by FACS as Flk1+/cKit+/CD45-SP cells, and we have shown that these cells give rise to HSPC contained within the Flk1-/cKit+/CD45+ SP fraction of yolk sac and AGM cells 5,11,12 . Hemogenic endothelial cells and HSPC can be identified and isolated from yolk sac or AGM tissues harvested from either freshly euthanized embryos, or from embryos cultured for up to 48 hours in ex vivo embryo culture (as depicted in Figure 1).…”
Section: Introductionmentioning
confidence: 98%
“…Towards this goal, we have defined the phenotype of hemogenic endothelial cells, on a clonal level, within the murine yolk sac 11 and AGM 12 , two major sites of definitive HSPC production during embryogenesis. Like HSPC within adult bone marrow 17 , embryonic hemogenic endothelial cells and HSPC exhibit Hoechst dye efflux properties and therefore appear within the "side population" (SP) of cells on a FACS plot 5,11,12 (as shown in Figure 3). In addition, we have also shown that hemogenic endothelial cells express markers of both endothelial and stem cells (Flk1 and cKit, respectively), but do not express the hematopoietic lineage marker, CD45 5,11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HSC are derived from mesoderm 5 . The hematopoietic progenitors accumulate around the blood islands initially, migrating to the fetal liver reaching the bone marrow 6,7 .…”
Section: Introductionmentioning
confidence: 99%